Pemanfaatan Penggunaan dan Pengoperasian Mesin Otomatis pengelolaan Sampah Botol Plastik (RVM) pada Masyarakat berbasis Ekonomi Sirkuler di kota D.I Yogyakarta - Elyzabeth Eka Nurmelasari; Wahyu Fahrul Ridho (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Utilization in managing plastic bottle waste using an automated Reverse Vending Machine (RVM) machine is a new introduction to society, especially in the city of Yogyakarta. This study aims to reduce plastic bottle plastic waste in the Yogyakarta city environment by operating a Reverse Vending Machine automation machine by describing the linkages with the circular economy at the community level around the city of Yogyakarta. One of the economic models offered by the world is the circular economy model, in which goods that have been consumed can be reprocessed. Meanwhile, plastic waste still has economic value which can be utilized by recycling but is constrained by the lack of public awareness. The purpose of this design is to design a recycling facility with new innovations and the right use to minimize the problem of inorganic waste in an effective way, namely in the form of a Reverse Vending Machine specifically for plastic bottle waste. The conclusion of this design is intended to utilize plastic bottle waste in the city of Yogyakarta which still has economic value by means of the recycling process using a circular economic model based on the canvas business model.